The effect of agricultural technology on the speed of development - Eberhardt, Markus; Vollrath, Dietrich (Elsevier, 2018)
We examine heterogeneity in the elasticity of agricultural output with respect to labor. Employing panel data from 128 countries over a forty year period we find distinct heterogeneity in the elasticity of agricultural output with respect to labor. This elasticity is lowest in countries with temperate and/or cold climate regions, and higher in countries including tropical or highland regions. This agricultural parameter determines the speed of structural change following changes in agricultural productivity or population. Calibration shows shifts in labor allocations and welfare will be 2–3 times larger in temperate regions than in tropical or highland regions.